Monetary Policy, Macroprudential Policy, and Credit Cycle: Evidence in the Indonesian Banking Industry - Anwar, Cep Jandi; Didu , Saharuddin; Suhendra, Indra; Ichwanudin, Wawan; Nupus, Hayati (International Journal of Economics and Financial Issues, 2025)
This research aimed to analyse the effect of monetary policy and macroprudential policy on credit cycle for 41 conventional banks between 2010 and 2023 in Indonesia. Initially, four models using POLS and fixed effect models were executed in this paper. Subsequently, a Durbin-Wu-Hausman test identified issues of endogeneity in the models. Ultimately, a panel GMM estimation was employed. The findings revealed that central bank rate had a positive influence on credit cycle. While macroprudential policy had a negative impact on credit cycle. The interaction effect of macroprudential and monetary policies had an influence on lowering the credit cycle. The credit cycle is influenced negatively and significantly by Non-performing loans (NPL) and capital adequacy ratio (CAR). Meanwhile, inflation, economic growth and loan-to-deposit ratio (LDR) had a positive effect on the variable. The findings offer valuable policy insights for policymakers in Indonesia. Central banks should be aware of how banks’ credit cycles behave in response to shocks from monetary and macroprudential policies.